Trajectories of Salivary Hormones in Pregnant Women with Anxiety and there Effect on Gingival Health Condition - Noor Majid Hameed; Athraa Mustafa Alwaheb (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Hormonal fluctuations during pregnancy caused several of the physiological changes designed for promoting growth and delivery of a healthy child. A delicate balance between immune tolerance to fetal antigens and immunity against infectious pathogens needs to be maintained.Aim: Assessing salivary cortisol and progesterone hormones in anxious pregnant women and their impact on gingival health status.Subjects and Method:A sample of 80 womenwith healthy pregnancy divided into two groups including 40 pregnant women with high anxiety levelmatch in age with40 pregnant womenhavea low level of anxietyin Baghdad Teaching Hospital of Baghdad city in Iraq were participated in this study. Plaque index was used for assessing dental plaque accumulations.The gingival conditionwasmeasured by the gingival index.Unstimulated saliva sample was collected for measuringsalivary cortisol and progesterone.Result: The strong validity and reliability of Beck Anxiety Inventory (BAI) Arabic translationscale make ita good indicator for measuring anxiety in Iraqi pregnant women.Data analysis of this study revealed high anxiety group has an elevated level of salivary cortisol, decrease salivary progesterone withsignificant differences. The correlations coefficients between salivary cortisol and progesterone among the high anxiety group was negative strong significant correlation while non-significant correlation in low anxiety group.The plaque indexwas higher among the high anxiety group with significantdifferences. Concerning the gingival index; there isno significant differences among two group. Positive strong significant correlation between plaque and gingival indices in high anxiety group.Regarding the correlation between gingival index and salivary progesterone in low anxiety group, it waspositive strong significant.While a positive significant correlation between plaque index and salivary cortisol in both groups.Conclusion: This study reported increase stress-hormone cortisol among a high anxiety pregnant women which hasan effect ongingival health subsequently. Gingival inflammation in the high anxiety group was a plaque induce gingivitis, while a pregnancy gingivitis was found among the low anxiety group